Cassava agronomy research in Asia: An overview 1993-1996 - Howeler, Reinhardt H. (International Center for Tropical Agriculture, 1998)
During the past three years (1993-1996), cassava agronomy research, conducted by national programs in collaboration with CIAT and with financial support from the Nippon Foundation in Japan, continued as before but at a slightly lower level of activity. Major emphasis remained on soil fertility maintenance and erosion control with the objective of enhancing the sustainability of cassava production in Asia. Long-term fertility trials have been conducted in 14 locations in four countries. Some of these trials are now in the 8th or 9th cycle of continuous cassava production. During the latest crop cycle there was a significant response to N in ten sites, to P in six sites and to K in eleven sites, indicating the importance of adequate fertilization of cassava with K and N and a lesser need for P. Especially the response to K increased with successive cassava cropping cycles. Various types of erosion control trials were continued in 13 sites in five countries. Research in Thailand indicate that time of planting has a strong influence on erosion, with greatest soil lasses occurring when cassava is planted in the beginning of the rainy season. For cassava monoculture the planting on contour ridges, at closer spacing and with adequate fertilization increased yields and reduced erosion losses. Among various intercropping systems the interplanting of peanuts is generally most effective in reducing erosion, while also providing a good additional income. Intercropping with pumpkin or squash was also quite effective, but watermelons, cucumbers or muskmelon were more difficult to establish. Among various contour barriers tested, the most suitable were hedgerows of Flemingia congesta and Gliricidia sepium in Malang, E. Java, Gliricidia and Leucaena leucocephala in South Vietnam, Thephrosia candida in North Vietnam, and vetiver grass in Nanning, China, and in Leyte, Philippines; application of grass mulch was even more effective at the latter location. The efficiency of hedgerows of many other grass species are presently being investigated in Thailand. Maintaining soil fertility with no or little chemical fertilizers is being investigated in South Vietnam, Indonesia and Thailand. A crop rotation of cassava with peanut/pigeon pea was found to be effective in northeastern Thailand. Green manuring with Crotalaria juncea or Canavalia ensiformis before planting cassava (cassava harvested after 18 months for a 2-year cycle), or interplanting these same two species and cutting and mulching the legumes at 2 MAP for a 12-month cassava crop, were found to be most effective in maintaining high yields when only small amounts of fertilizers were applied. A similar intercropping/mulching treatment with Tephrosia Candida was also effective in South Vietnam, although intercropping and mulching with cowpea was even more effective. Weed control trials have been conducted in Thailand and are being initiated in South Vietnam. The preemergence herbicide Metolachlor seems effective in both locations and can also be used when cassava is intercropped with mungbean or peanut. The frequency and cost of weeding was markedly reduced when cassava was planted at the end rather than the beginning of the rainy season in Thailand. More efficient methods of weed control, both chemical and mechanical, need to be further investigated as labor for hand weeding is becoming more and more expensive.